Πολυπολιτισμικό σχολείο : κοινωνικές σχέσεις και σχολικές επιδόσεις - Μια εμπειρική έρευνα - Παπαδόπουλος, Αναστάσιος - Απόστολος (2015)
In the education field, the phenomena of immigration and repatriation in Greece have significantly changed the demographics of many schools in various areas. It is estimated that students who are "non-Greek" speakers surpass 12% of the total student population.The challenge is immense, still the indications are discouraging. The research results of the Programme of International Student Assessment (PISA 2000, 2003, 2006) revealed that the performance of foreign students - a considerable component of the greek school - is inferior to the performance of Greek students. Other studies have also indicated that immigrant students have low self-esteem, while many abandon school.Research aims and objectives.The aim of this research is to explore attitudes and perceptions of students in primary education multiculturalschools towards their classmates, teachers and school environment. Other objectives of the research were a) theexamination of differences in social relationships, social acceptance and grading among native and immigrant students.b) the investigation of students'attitudes towards social acceptance and school grades, c) the study of differences among students of different sex concerning their relationships, social acceptance and grading, d) The impact of the classroom on social relationships, social acceptance and students'grades.The main inquiries of the research were the following:1) What are the differences among students of different nationality (native - foreign) concerning their social relationships,degree of social acceptance and their grades?2) What is the correlation between students'attitudes and social acceptance?3) Are grades connected with the students' social acceptance and social relationships?4) Are there any alterations in students' social relationships degree of social acceptance and school grades of students of different sex?Research participants One hundred and seventy (170) primary education students from urban and suburban Athens. The results of the analyses have indicated the existence of statistically important correlations among the following factors, a) acceptance from classmates, b) school fear, c) self-esteem, d) interest for school.